2021
DOI: 10.4018/ijssci.2021070101
|View full text |Cite
|
Sign up to set email alerts
|

Recurrent Neural Network (RNN) to Analyse Mental Behaviour in Social Media

Abstract: A recent British study of people between the ages of 14 and 35 has shown that social media has a negative impact on mental health. The purpose of the paper is to detect people with mental disorders' behaviour in social media in order to help Twitter users in overcoming their mental health problems such as anxiety, phobia, depression, paranoia. The authors have adapted the recurrent neural network (RNN) in order to prevent the situations of threats, suicide, loneliness, or any other form of psychological proble… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
7
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
5
1
1

Relationship

0
7

Authors

Journals

citations
Cited by 36 publications
(8 citation statements)
references
References 11 publications
0
7
0
Order By: Relevance
“…Some recent studies have shown that there is a huge negative impact on the mental health of the user on social media. Bouarara 202 proposed a technique for detecting psychological disorders' of Twitter users by analyzing their tweets and using recurrent neural networks (RNN). Chen et al 203 also designed a framework for checking the psychological characteristics of an OSN user and predicting his/her consumption behaviors by analyzing his/her marketing mining data.…”
Section: Ml‐based Solutions For Osn Platformmentioning
confidence: 99%
“…Some recent studies have shown that there is a huge negative impact on the mental health of the user on social media. Bouarara 202 proposed a technique for detecting psychological disorders' of Twitter users by analyzing their tweets and using recurrent neural networks (RNN). Chen et al 203 also designed a framework for checking the psychological characteristics of an OSN user and predicting his/her consumption behaviors by analyzing his/her marketing mining data.…”
Section: Ml‐based Solutions For Osn Platformmentioning
confidence: 99%
“…Sahoo et al focused on the detection of fake news in OSNs 18 and proposed an approach for fake news detection on Facebook in which multiple features associated with Facebook accounts were incorporated and analyzed through deep learning. Aiming at helping users in OSNs to deal with mental health issues, Bouarara proposed an approach to identifying people with the behavior of mental disorders in OSNs 19 in which the recurrent neural network (RNN) was adopted and shown to exhibit some advantages. Deep learning has provided a new direction for private inference, making it worthwhile to design deep learning based methods in private inference to improve both effectiveness and efficiency.…”
Section: Related Workmentioning
confidence: 99%
“…People are increasingly reliant on the Internet for information and also to fulfill other social needs. Scholars have conducted a series of studies based on big data on the Internet, such as sentiment analysis using big data to forewarn users of mental health problems ( Mohammed et al, 2022 ; Bouarara, 2021 ), account security ( Masud et al,2020 ), construction of identification systems ( Campomanes-Alvarez et al, 2019 ), conducting academic research ( Tembhurne et al, 2022 ; Fayoumi & Hajjar, 2020 ; Noor et al,2020 ), and even to predict global sustainable development goals ( Chopra et al, 2022 ), and a host of other issues.…”
Section: Introductionmentioning
confidence: 99%